The temperature of cremation and its effect on the microstructure of the human rib compact bone - Absolonová, Karolina; Dobisiková, Miluse; Beran, Michal; Zocová, Jarmila; Velemínský, Petr (Anthropologischer anzeiger, 2012)
The presented study deals with the effect of the cremation temperature on the microstructure and morphology of the human compact bone. The biological material consisted of samples from ribs of recent Central European origin belonging to individuals of known age, sex and cause of death. Each bone sample was divided into several sections. One section remained unburned and the rest were burned at 700, 800 and 1000 degrees C. A few samples were burned also at the temperature of 600 degrees C. The undecalcified unstained ground cross-sections were made from burned and unburned bones; photographed and analysed using the SigmaScan Pro 5 programme. During burning, both the macroscopic and microscopic dimensions of the bone shrink, including the measures of the individual microstructures. The percentual representation of the area of individual microstructures on the area of the cross-section decreases. The number of individual microstructures per mm2 of the compact bone cross-section increases. Most microstructural variables demonstrated statistically significant differences at the individual temperatures of cremation. The burned bones showed a large scale of the colours, especially at 700 degrees C.
Keywords: Histocytochemistry; Ribs; dospělí; Hot Temperature; antropologie fyzická; lidé; žebra; mužské pohlaví; Anthropology, Physical; Male; vysoká teplota; Cremation; Adult; histocytochemie; kremace; Humans